Russian "émigré" culture: conservatism or evolution? - Flamm, Christoph; Keazor, Henry; Marti, Roland (Cambridge Scholars Publishing, 2013)
A quarter of a century ago, glasnost opened the door for a new look at Russian émigré culture unimpeded by the sterile concepts of Cold War cultural politics. Easier access to archives and a comprehensive approach to culture as a multi-faceted phenomenon, not restricted to single phenomena or individuals, have since contributed to a better understanding of the processes within the émigré community, of its links with the lost home country, and of the interaction with the cultural life of the c...
Includes index. - Description based on online resource; title from PDF title page (ebrary, viewed July 24, 2014)
Keywords: Electronic books; Aufsatzsammlung; Konferenzschrift -- 2011 -- Saarbrücken; Europa; Verbreitung; Auswanderer; Musik; Kunst; Literatur; Russland